Effect of The Board of Director's Characteristic On Islamic Bank's Financial Soundness : english - Afef Khalil (Tazkia Islamic Finance and Business Review, 2021)
The aims of this study is to diagnose the Board of Director’s characteristics and its impact on the financial soundness of Islamic banks. Regression analysis are applied to test the effect of the Board of Director's characteristics on the financial soundness of Islamic banking, employing a panel data composed of 67 Islamic banks during the period 2005-2014. The level of Islamic bank soundness is individually using the Z-score indicator. To verify the robustness of results, we use other dependent variables (CAMEL) than the Z-score for the year 2018. Results show that the independent non-executive director, the foreign director and the institutional director, have a negative and significant impact on the financial soundness of Islamic banks. While, the Board of Director’s size does not have any significant effect on the financial soundness of Islamic banks.This research contributes to fill the gaps in the literature that discussed the Board of Directors’ role in the corporate governance of Islamic banking. In other words, it shows the role played by the Board of Director and improves our knowledge of the financial soundness-corporate governance relationship. With this paper, we hope to clarify the relationship between the Board of Director and the financial soundness of Islamic banks and provide new insights to the literature review. This study offers practical and valuable implications for banking associations, researchers and regulators. In other words, in addition to its theoretical and scientific value, this paper is practical and useful for professionals.     Keywords: Board of Director, Corporate Governance, Financial soundness, Islamic Bank